DETERMINING THE POSSIBILITIES OF DEVELOPING PHYSICAL QUALITIES THROUGH PEDAGOGICAL ANALYSIS OF THE MORPHOFUNCTIONAL AND PSYCHOPHYSIOLOGICAL PROPERTIES OF YOUNG ATHLETES (Universal International Scientific Journal, 2026)
This article is dedicated to the scientific study of opportunities for the effectivedevelopment of physical qualities in young track and field athletes through a systematic pedagogicalanalysis of their morphofunctional and psychophysiological characteristics. The study evaluatedathletes’ body structure, muscle system functions, cardiovascular and respiratory indicators, as well aspsychological parameters, including motivation, attention, and stress resilience.
Keywords: Athletics; young athletes; morphofunctional characteristics